2015
DOI: 10.1108/jic-02-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Government policy implications of intellectual capital: an Australian manufacturing case study

Abstract: Purpose – The purpose of this paper is to report on an industry policy implementation case involving around 30 manufacturing firms, where the intellectual capital (IC) lens, and especially the intellectual capital navigator (ICN) approach, was found to be very useful for evaluating alternative servitisation strategies. Servitisation is a form of business model innovation and as such involves restructuring the firm’s resource deployment system including its IC resources. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…It allows firms to preserve their evolutionary fitness [94]. Intellectual capital a vital knowledge-based asset that acts as the source of routines and production processes in a firm and the capabilities and core competencies that can improve a firm's performance [95]. To sustain profitable growth, the firm requires all the assets to be reconfigured and recombined during the evolving technologies and market [46].…”
Section: Implication Of Reconfiguring Capability On the Relationship Between Intellectual Capital And Innovation Performancementioning
confidence: 99%
“…It allows firms to preserve their evolutionary fitness [94]. Intellectual capital a vital knowledge-based asset that acts as the source of routines and production processes in a firm and the capabilities and core competencies that can improve a firm's performance [95]. To sustain profitable growth, the firm requires all the assets to be reconfigured and recombined during the evolving technologies and market [46].…”
Section: Implication Of Reconfiguring Capability On the Relationship Between Intellectual Capital And Innovation Performancementioning
confidence: 99%
“…The most recent studies of the evolution of IC point out a taxonomy based on four stages of IC development (Roos and O'Connor, 2015;Pedro, Leitao, and Alves 2018;Borin and Donato, 2015;Secundo et al, 2018;Stahle and Bounfour, 2008) (Warner and Wäger, 2019;Nambisan at al., 2019). In entrepreneurship literature this is mostly celebrated for facilitating entrepreneurial opportunity, new business models, innovations and value creation (Nambisan at al., 2019) but also receive many critics for "platformisation" of society with many negative consequences (van Dijck et al, 2018;Srnicek, 2016).…”
Section: The Concept Of the National Intellectual Capital (Nic)mentioning
confidence: 99%
“…Recent studies, in the field of research on IC, have identified a taxonomy of three temporal phases and the beginning of a fourth (Guthrie et al , 2012; Dumay and Garanina, 2012, 2013; Labra and Sánchez, 2013; Roos and O’Connor, 2015). Nevertheless, all the stages can be considered as being under development.…”
Section: Scope Of the Reviewmentioning
confidence: 99%